Exploring body dissatisfaction in pregnancy and the association with gestational weight gain, obesity, and weight stigma. (April 2023) - Hill, Isabelle F.; Angrish, Kirina; Nutter, Sarah; Ramos-Salas, Ximena; Minhas, Harneet; Nagpal, Taniya S.
Abstract: Objective: Body dissatisfaction in pregnancy has been associated with negative psychological maternal outcomes, including increased risk of postpartum depression. This study aimed to explore weight-related factors that influence body dissatisfaction in pregnancy, including gestational weight gain (GWG), weight stigma, obesity, and weight loss attempts before pregnancy. Design: Secondary analysis of a larger cross-sectional study. Setting: Online survey administered via Qualtrics. Participants: ≥12 weeks pregnant, ≥18 years of age, having a singleton pregnancy and residing in Canada. Measurements and Findings: A battery of questionnaires were completed, including the Body Image in Pregnancy Scale (BIPS) sub-scale. The BIPS scores were compared based on experiences of weight stigma in pregnancy, perception towards their GWG, weight loss attempts before pregnancy, obesity, and GWG category classified as excessive or not referring to Institute of Medicine (2009) guidelines. Significant differences were entered into a linear regression model with BIPS scores as the dependent variable. Significance was accepted as p <0.05. A total of 182 participants completed the survey. There were no differences in BIPS scores based on GWG category ( p  = 0.160), or obesity ( p  = 0.230). Poorer BIPS scores were reported by those who felt they had gained 'too much' pregnancy weight than 'appropriate' ( p <0.001), and among those who were trying to lose weight before pregnancy compared to those who were not ( p  = 0.002). Poorer BIPS scores were also reported by individuals who indicated they had experienced weight stigma during pregnancy compared to those who had not ( p <0.001). Regression results showed that significant variables were perceptions towards GWG ( p  = 0.003) and experiencing weight stigma in pregnancy ( p  = 0.011). Key Conclusions and Implications for Practice: Perceptions towards GWG and experiencing weight stigma can influence body dissatisfaction in pregnancy. Given the detrimental physical and psychological consequences of body dissatisfaction, effective strategies to reduce prenatal weight stigma are needed, such as training maternal healthcare providers to offer sensitive preconception and prenatal weight counselling.